Exploring the Psychological Mechanism of Digital Media on Consumer Brand Awareness in the Context of Global Communication Environment - Sha, Yuran (International Journal of Social Sciences and Public Administration, 2024)
In the context of global communication, digital media has become the main channel for consumers to obtain brand information, profoundly influencing their perception of the brand. This article first briefly describes the concept of brand cognition, and introduces the psychological mechanism of the impact of digital media on consumer brand cognition in the context of global communication environment, from three aspects: the fundamental role of sensory cognition, the additional role of brand knowledge, and the overlapping role of product experience. Finally, three main marketing strategies for digital media in the current global communication environment were introduced: precise targeting of target customers, emphasis on information dissemination, and the combination of online and offline channels. The content of this article can provide some reference for related research.